2023
DOI: 10.1002/adsc.202201340
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of o‐Bis(3‐indolyl)arenes under Brønsted Acid Catalysis: Carbonyl Compounds as Sources of Aryl Groups

Abstract: A method of synthesizing o-bis(3-indolyl)arenes was developed by reacting indoles with 7oxabicyclo[2.2.1]hept-5-en-2-one and derivatives thereof having no aromatic ring. All 23 unknown o-bis(3indolyl)arenes could be obtained using this method. Palladium catalysis is useful for enlarging the πconjugated area of o-bis(3-indolyl)arenes, delivering aryl-, alkynyl-, and alkenyl-unit-installed o-bis(3indolyl)arenes, and benzo[c]indolo[2,3-a]carbazoles, the derivatization to which is effective for raising fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The outcomes of the reaction between indoles and 2‐chlorocyclohexanone are diverse, with minor changes leading to different products [9d] . In our previous report, we found that α ‐indolic ketone is quantitatively generated under basic reaction conditions (Scheme 2, 3 a ) [13] .…”
Section: Resultsmentioning
confidence: 96%
“…The outcomes of the reaction between indoles and 2‐chlorocyclohexanone are diverse, with minor changes leading to different products [9d] . In our previous report, we found that α ‐indolic ketone is quantitatively generated under basic reaction conditions (Scheme 2, 3 a ) [13] .…”
Section: Resultsmentioning
confidence: 96%
“…Boronate compounds are a kind of highly attractive compounds that are widely used in organic synthesis, catalysis, supramolecular chemistry, biology, and medicine. [ 10–15 ] Recently, benzoxaborole‐diol complexations, which are formed by dynamic covalent bonds between a series of five‐membered heterocyclic compounds containing a boron atom and 1,2 or 1,3‐diols in neutral or weakly alkaline media, have received increasing attention in the medical field as a new versatile scaffold with plenty of pharmacological activities. [ 16–18 ] Also, it should be noted that the complexation of benzoxaborole‐diol is a class of structural units that is sensitive to various external triggers, including diols, catechol, pH, and H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Boronate compounds are a kind of highly attractive compounds that are widely used in organic synthesis, catalysis, supramolecular chemistry, biology, and medicine. [10][11][12][13][14][15] Recently, benzoxaborole-diol complexations, which are formed by dynamic covalent bonds between a series of five-membered heterocyclic X. Zhang, Y. Chen Xi'an Peihua University Medical College Xi'an, Shaanxi 710125, P. R. China E-mail: 003414@peihua.edu.cn…”
Section: Introductionmentioning
confidence: 99%